Managing PBL difficulties in an industrial engineering and management program - A. C. Alves; Rui Sousa; Francisco Moreira; M. Alice Carvalho; Elisabete Cardoso; Pedro Pimenta; Teresa Malheiro; Irene Brito; Sandra Fernandes; Diana Mesquita (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Project-Based Learning (PBL) is considered to be an active learning methodology which can be used to develop both technical and transversal competences in engineering programs. This methodology demands a great deal of work effort from the students and also from the teachers and it requires a meticulous plan and a well-managed project as well. These activities go far beyond the normal activities in traditional lectures, enabling to outpace the difficulties that spur along the way that may be both complex and demotivating. This methodology has been implemented in the Integrated Master Degree on Industrial Engineering and Management (IEM), at one public university in Portugal, since the 2004/2005 academic year. The aim of this paper is to identify and discuss the main difficulties of the implementation of PBL, mainly from the teachers' perspectives. Additionally, some effective strategies will be recommended to overcome such difficulties. Design/methodology/approach: The perceptions of the teachers were collected through a survey based on six main themes. The participants in the study include eight teachers from the five courses of the first semester of the first year of the IEM program involved in the 2012/2013 and 2013/2014 editions. Findings: Integration of courses in the project; student assessment; growing number of students in each team and the need of physical spaces for them; and compartmentalized knowledge has emerged as the main difficulties. To overcome these difficulties some key strategies were recommended. Originality/value: A new perspective based on course teachers' views and experiences will deepen the understanding of the problems and provide inputs for the development of strategies that may improve the effectiveness of PBL and introduce changes for its successful implementation. These strategies are intended to be transferable to other contexts, as most of the problems and constraints are common to other active learning approaches.
Keywords: 650; project-based learning; active learning; engineering education; industrial engineering and management curriculum